ANALISIS MINTA MASYARAKAT KECAMATAN PEMENANG BARAT DALAM MENGGUNAKAN BANK SYARIAH - Nurhayati; Erwin Saputra Siregar (ICONS: Islamic Economics Journal, 2026)
This study aims to analyze the interest of the community in Pemenang Barat District in using Islamic banking services. The research employed a qualitative approach with data collected through in-depth interviews with local residents. The findings indicate that the community’s interest is influenced by several key factors, including their level of knowledge regarding Islamic banking principles, prior experiences with sharia-compliant products, the religious values they uphold, and social support from their environment. Furthermore, service accessibility and outreach efforts by Islamic banks also play significant roles in enhancing community interest. Based on these findings, it is expected that Islamic banks will intensify educational initiatives and expand service coverage so that more people will  be  encouraged  to  shift  to  the  Islamic  banking  system.